Institutional Traps of Digitalization of Russian Higher Education - M. A. Golovchin (Высшее образование в России, 2021)
In 2016-2018 the state in Russia adopted a package of program documents, which implies the transfer of education to the large-scale introduction of digital technologies. This phenomenon has been called “digitalization of education”. In scientific literature, electronization and digitalization are increasingly called one of the institutional traps for the development of Russian universities, since the corresponding institutional environment has not yet been formed due to the forced nature of innovations. As a result, the processes of introducing new technologies into education are still not regulated. Within the framework of the purpose of the study, the manifestations of the trap of electronization and digitalization of Russian higher education were analyzed on the basis of sociological data, and the theoretical modeling of the process of adaptation of educational agents to the institution of digitalization was carried out.In the course of the study, the approaches were summarized that have been developed in discussions on educational digitalization. The article presents the author’s vision of the studied phenomenon as an institutional trap; as well as understanding of the institutional features and characteristics of electronization and digitalization in education.The research method is the analysis of estimates obtained in the course of an expert survey which was conducted by the Vologda Scientific Center of the Russian Academy of Sciences among the representatives of the teaching staff of state universities in the Vologda region. In the course of this analysis, the indicators of educational digitalization as an effective innovation were clarified such as an increased accessibility of educational resources; simplification of communication and the process of transferring knowledge from teacher to student; increased opportunities for training specialists for the new (digital) economy; improving the quality of education in universities, etc. Based on the results of the empirical study, it has been determined that the conditions for the development of digitalization in Russian universities are currently ambiguous, which is closely related to the level of competitiveness of the educational organization.The scientific novelty of the research consists in the presentation of an original matrix describing the process of university employees adaptation to the conditions of digital transformation of education. The matrix is proposed on the basis of a sociological analysis of the impact of the trap of electronization and digitalization on the activities of educational agents. The matrix can be taken into account in the practice of higher education management.